FACTORS INFLUENCING THE DECISION TO PURCHASE HALAL-LABELED FOOD PRODUCTS AMONG THE PEOPLE OF SENYERANG SUB-DISTRICT - Zuhratul Aulia; Syafruddin; Ahmad Ridwan; Nurleni (Adisam Publisher, 2024)
Indonesia with the majority of Moslem population becomes the very potential market for the producers of goods and service. Though the customers have the different levels of obedience towards law dependent upon the level of their religiosity, they have a positive attitude towards the products using the halal approach in their marketing. Along with the increase of the number of Moslems in Indonesia, study in the context of acknowledgement towards the Halal products needs to be examined further. The halal products must be acknowledged as the symbol of cleanness, safety, and high quality for the Moslem customers. The results showed, there are 4 factors that can be analyzed in the decision to purchase food products labeled halal among the Senyerang community, namely 1) religious factors, 2) psychological factors, 3) social factors . 4) factors of culture.